Nature of potential families from elastic 16O +16O rainbow scattering*Dedicated to the loving memories of F Bary Malik for inspiring us to use NM potentials; and Devika Basak, who was not only the loving wife of our group leader (AKB), but a source of extraordinary care, affection and inspiration for all his students and colleagues, sadly leaving us on 18 November 2020, just weeks before this article was accepted. (11th June 2021) - Islam, M Sujan; Ramon, R A; Rahman, M Mizanur; Majumder, R; Sayed, M A; Nilima, A; Azad, M M B; Tariq, A S B; Uddin, M A; Basak, A K
Abstract: The experimental differential cross-sections of 16 O + 16 O elastic scattering in the energy range 75 MeV ⩽ E lab ⩽ 1120 MeV are analysed using families of non-monotonic (NM) shallow nucleus–nucleus potential in the framework of the optical model. The experimental data is reproduced successfully using six families of NM potentials. It is found that all families converge at 350 MeV. The clear indication of the convergence of the potential families at 350 MeV conforms to the Goldberg criterion concerning the removal of discrete ambiguities even for the shallow NM potential. The study further suggests that the energy of convergence heralds the occurrence of the primary rainbow at that incident energy.